Finding a path - understanding the employment, demands and preparation for high-performance rugby union coaching - Taylor, J.; MacNamara, Á.; Sheridan, D.; Turkington, J.; Taylor, R. (Sports Coaching Review, 2025)
Developing high-performance (HP) coaches remains a challenge for sporting bodies with limited guiding research. This study, integrated multiple perspectives and methodologies, examined the transition to HP coaching to inform Irish Rugby`s coaching support. It involved three stages: (1) semi-structured interviews with recruiters (N=8) to explore employment factors, (2) Applied Cognitive Task Analysis with HP coaches (N=5) to understand cognitive demands, and (3) simulation interviews with aspiring HP coaches (N=10) to assess role readiness. Analysis used reflexive thematic analysis (1) and integrative qualitative content analysis (2/3). Recruiters prioritised credibility, breadth and depth of coaching skill and organisational ?t in employment decisions. HP coaches experienced a range of cognitive demands including managing pressures, building credibility, sta? contributions and pedagogical and tactical challenges. In contrast, aspiring coaches underestimated contextual demands, focusing on procedural tasks and personal affinity. Guided cognitive apprenticeships, incorporating modelling, scaffolding, and social capital development, are recommended to support transitioning coaches.